Twin-lattice atom interferometry - Martina Gebbe (Nature Portfolio, 2021)
Atom interferometers can be useful for precision measurement of fundamental constants and sensors of different type. Here the authors demonstrate a compact twin-lattice atom interferometry exploiting Bose-Einstein condensates (BECs) of 87 Rb atoms.